Doxa and Arete in Isocrates' Pedagogy - Held, Klaus (1999)
Isocrates was Plato's main rival as school founder. The first part outlines the primordial significance of Isocrates for European "humanism." The second part explains the wide-ranged concepts where with lsocrates grounds his rethoricles son, specially in his programmatic writing, Against Sophists. In the third part is explicated why Isocrates, unlike Plato, places and what that means methodologically. From these premisses the fourth part draws consequences for the understanding of apettí in Isocrates' idea of education, and shows how it prepares Aristotle's ethics.